GSK3: a SHAGGY frog story. - Welsh, G.I.; Wilson, C.; Proud, C.G. (Trends in Cell Biology, 1996)
Glycogen synthase kinase 3 was discovered in mammals several years ago but only recently has it become clear that this enzyme is acutely regulated by hormones such as insulin and by growth factors. In mammals, it appears to be controlled by a signalling pathway linked to phosphoinositide 3-kinase and may regulate a range of biosynthetic processes. Evidence is now accumulating that GSK3 plays a key role in the regulation of cell fate and differentiation in many eukaryotic species.